2012
DOI: 10.1039/c1nr10742a
|View full text |Cite
|
Sign up to set email alerts
|

High-yield synthesis of ZnO nanowire arrays and their opto-electrical properties

Abstract: In this article, ZnO nanostructures were synthesized via the hydrothermal method which used ZnCl(2) and HMTA mixed solution as the precursor. A multistep growth was adopted to improve the growth restriction of a closed system, not only the length but also the aspect ratio were increased with steps of growth, and the shape of nanorods maintained integrity. Furthermore, photoluminescence spectra which have the near-band-edge-emission (∼3.37 eV) and defect-related emission show the optical properties of ZnO nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Among them, hydrothermal method is an economical and low-temperature fabrication method. However, the large defect concentration is inevitable for the synthesis of ZnO nanowires during a low-temperature hydrothermal route, such as surface defects, near surface traps and surface adsorbed species [5,6], which maybe result in passivation or inefficient electron transport [7]. In general, a post annealing treatment is a effective way to modify the surface defects.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, hydrothermal method is an economical and low-temperature fabrication method. However, the large defect concentration is inevitable for the synthesis of ZnO nanowires during a low-temperature hydrothermal route, such as surface defects, near surface traps and surface adsorbed species [5,6], which maybe result in passivation or inefficient electron transport [7]. In general, a post annealing treatment is a effective way to modify the surface defects.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested growth occurred from solutions supersaturated with respect to Zn(OH) 4 2-. 25 The occurrence of a hexagonal prismatic morphology [26][27][28][29][30][31] is generally assumed to be a consequence of surface energy effects favouring the development of {10-10} and {0001} crystal faces.…”
Section: Introductionmentioning
confidence: 99%
“…A portion of holes are drifted by the surface electric field in the depletion layer. The migrated holes can neutralize the surface adsorbed oxygen and resulting in the decrease of depletion layer near the surface [27].…”
Section: Resultsmentioning
confidence: 99%
“…The fast UV response may be attributed to the adsorption and photodesorption of oxygen molecules on the surface of ZnO thin films. Before UV irradiation, oxygen molecules are adsorbed onto the surfaces of ZnO thin film by capturing free electrons from the ZnO and forming a low-conductivity depletion layer near the surface [27]. …”
Section: Resultsmentioning
confidence: 99%